Pengaruh Pemberian Dehydrepiandrosterone (DHEA) Terhadap Paru-Paru Tikus Wistar Jantan Yang Terpapar Asap Rokok - Sri Hardiyanti Asad; Aryadi Arsyad; Yulia Yusrini Djabir (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2022)
This study investigated the effect of dehydroepiandrosterone on the lungs of male Wistar rats exposed to cigarette smoke. A total of 21 male Wistar rats were divided into 3 groups, namely the first group (negative control exposed to cigarette smoke for 14 days), the second group (given DHEA at a dose of 15 mg/kgBW and exposure to cigarette smoke), the third group (given DHEA at a dose of 30 mg/kgBW and exposure to cigarette smoke). DHEA was administered orally through a cannula 30 minutes before exposure to cigarette smoke with an exposure duration of about 25-40 minutes, equivalent to 4 cigarettes/day. After 14 days of experimentation, the rats were euthanized. Right lungs were harvested for malondialdehyde level measurement using the thiobarbituric acid reactive substance method measured by UV-Visible spectrophotometer at a wavelength of 532 nm. The left lungs were also harvested for histopathological examination. This study showed that pulmonary malondialdehyde levels in second and third group tended to be higher than in first group. Meanwhile, histopathological examination showed that the percentage of lung tissue damage in second and third group tended to be lower than in first group. Thus, it can be concluded that DHEA at doses of 15 and 30 mg/kgBW tended to act as a pro-oxidant but might potentially improve lung histology due to cigarette smoke exposure.